Role of serum n-6 polyunsaturated fatty acids in the development of acute coronary syndromes. (11th May 2022) - Inoue, N; Morikawa, S
Abstract: Funding Acknowledgements: Type of funding sources: None. Background and Aims: n-3 polyunsaturated fatty acids (PUFAs) have an inhibitory effect against the development of coronary artery disease (CAD). However, whether n-6 PUFAs, dihomo-gamma-linolenic acid (DGLA), and arachidonic acid (AA) play a role in the development of CAD remains unclear. This study investigated the association between PUFAs and the risk of developing acute coronary syndrome (ACS) using the lipid and PUFAs data of patients who received percutaneous coronary intervention (PCI) for either non-emergent conditions (staged group) or ACS (ACS group). Methods: We retrospectively evaluated 433 patients who underwent PCI between 2014 and 2021. The patients were divided into the ACS group (n = 18) and the staged group (n = 132). The lipid and PUFAs values of each patient between the two groups were compared. Moreover, to investigate the correlation between n-6 PUFAs levels and ACS, the effects of confounding factors such as use of strong statins and low-density cholesterol (LDL-C) levels were adjusted. Results: The ACS group had higher n-6 PUFAs levels than the staged group (DGLA: 36.8 ug/mL vs. 29.6 ug/mL; AA: 203.3 ug/mL vs. 145.8 ug/mL). Furthermore, the analysis of covariance adjusted for LDL-C levels showed a significant difference between the two groups in terms of DGLA and AA levels. Conclusions: The n-3 PUFAs levels did not significantly differ between the staged and ACS groups. Moreover, the ACS group had higher DGLA and AA levels and lower n-3 PUFAs/AA ratios than the staged group. Therefore, excess n-6 PUFAs may be a risk factor for ACS.